Strategies for Improving Occupational Safety Culture at PT PLN Indonesia Power Generation Business Unit in the South Kalimantan and Central Kalimantan Work Areas - Randy Wahyu Perdana; Indrayatie, Eko Rini; Maulana, Arief Rahmad; Subagyo, Rachmat (Universitas Muhammadiyah Pontianak, 2026)
This study analyzes factors influencing occupational safety culture and formulates improvement strategies at PT PLN Indonesia Power Generation Business Unit in South and Central Kalimantan. Using a quantitative approach with SEM-PLS and SWOT analysis, key determinants identified include accident management, OSH participation, regulation awareness, and worker motivation. Supporting factors are PPE use, management commitment, and OSH prioritization, while reporting, training, and monitoring act as systemic reinforcements. Findings show safety programs are well-internalized, indicating that improvements should emphasize leadership, active participation, optimized reporting, and integrated OSH training, supervision, and motivation.